: Personal Factor Analysis as an Influence on Online Shopping Behavior of Vegetable Product Through Digital Marketing Platform - Windi Lestari; Laila Husin; Dwi Wulan Sari (Politeknik Pertanian Bogor, 2024)
This research aims to analyze the influence of consumer personal factors which include gender, age, education, finances, and employment on buying interest and factual purchases of organic vegetables as well as analyzing the organic vegetable market segment by examining the characteristics of consumers who buy organic vegetables online in Palembang to become as a recommendation for marketing strategies for organic vegetables. The subjects were consumers who bought organic vegetables online at 20 shops that provided online purchases which was 200 respondents in total. The analytical method is K-Means Cluster analysis with the help of the SPPS 27 program and PLS 3.2 Structural Equation Modeling (SEM) analysis. The results show that there is a significant or positive influence of age, education, financial and employment factors on personal factors, and overall personal factors have a significant influence on purchase intention and factual purchases. The consumer market segmentation for organic vegetable products is consumers in productive age, 21 to 60 years old, highly educated, and work as private employees, entrepreneurs, and civil servants and from Palembangese, Javanese, Sundanese, and Malay origins, having a total income of IDR. 2–5 million in range. Moreover, this research is expected to be applied by online organic vegetable sellers to reach bigger market especially to those located in Palembang.